Artemisinin resistance in the malaria parasite, Plasmodium falciparum, originates from its initial transcriptional response - Zhu, L; van der Pluijm, RW; Kucharski, M; Nayak, S; Tripathi, J; White, NJ; Day, NPJ; Faiz, A; Phyo, AP; Amaratunga, C; Lek, D; Ashley, EA; et al. (Springer Nature, 2022)
The emergence and spread of artemisinin-resistant Plasmodium falciparum, first in the Greater Mekong Subregion (GMS), and now in East Africa, is a major threat to global malaria elimination ambitions. To investigate the artemisinin resistance mechanism, transcriptome analysis was conducted of 577 P. falciparum isolates collected in the GMS between 2016–2018. A specific artemisinin resistance-associated transcriptional profile was identified that involves a broad but discrete set of biological functions related to proteotoxic stress, host cytoplasm remodelling, and REDOX metabolism. The artemisinin resistance-associated transcriptional profile evolved from initial transcriptional responses of susceptible parasites to artemisinin. The genetic basis for this adapted response is likely to be complex.